(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
Habitat fragmentation driven by agricultural expansion, human settlement, and linear infrastructure has isolated Asian elephant (Elephas maximus) populations across their range, creating a patchwork of subpopulations connected by increasingly narrow and degraded corridors whose effectiveness in maintaining genetic connectivity determines the long-term viability of the species in fragmented landscapes. This study characterised the population genetic structure, gene flow dynamics, and inbreeding status of 12 Asian elephant subpopulations across six corridor systems in southern India and Sri Lanka using genotyping-by-sequencing (GBS) of 248 individuals, yielding 28,484 SNPs after filtering. STRUCTURE analysis identified K = 6 genetic clusters corresponding broadly to the six corridor systems, with FST(overall) = 0.184 (95% CI: 0.162-0.208), indicating substantial genetic differentiation consistent with substantially restricted gene flow among subpopulations. Effective population sizes (Ne) estimated by linkage disequilibrium methods ranged from 24.4 (most isolated subpopulation; single railway-bisected forest fragment) to 284.4 (largest connected subpopulation; intact corridor), with 7 of 12 subpopulations showing Ne < 50 individuals, below the minimum viable population threshold for long-term persistence. Relatedness analysis (KING estimator) identified significantly elevated first- and second-degree relatedness in isolated subpopulations (mean r = 0.12 +- 0.04 vs. 0.04 +- 0.02 in connected subpopulations; t = 8.42, p < 0.001). Corridor quality index (CQI; integrating width, land use, and infrastructure barriers) was significantly positively correlated with inter-subpopulation genetic connectivity (EEMS estimated migration rates; r(S) = +0.84, p < 0.001). These results identify three corridors requiring urgent restoration and two subpopulations at immediate genetic rescue risk, providing a genomic evidence base for targeted elephant conservation investment under the IUCN Species Survival Commission Asian Elephant Action Plan.